Zur Solifluktionsgrenze in den Gebirgen Japans - Elfenberg, Ludwig (ERDKUNDE, 1977)
Japan may be divided into four periglacial morphological regions (fig. 2). Region 1 is an area of cool winters and heavy snowfall where periglacial forms seldom appear and then hardly ever below the timber-line. Region 2, in central Hokkaido, has a cold winter climate. In most parts the terrain in gently sloped and strongly influenced by periglacial processes. Region 3 is distinguished by a cool winter climate and little snowfall. Here, periglacial forms are not widely spread, but they reach far below the timber-line, e.g. in central Honshu by approx. 800 metres and in north-east Hokkaido by approx.1200 metres. In region 4, an area with a mild winter climate, periglacial forms are of little importance. In Japan the appearance of periglacial forms at a relatively low altitude and below the timber-line is related to the marked seasonal differences of temperature. At a level where woods can thrive in warm and humid summers, periglacial forms (especially sorted steps, -rings, -nets and stripes) may appear in relatively cold winters,provided that the soil is not protected by dense plant or snow cover. Therefore the lower boundary of the periglacial stage in Japan is more difficult to define than in European mountain ranges; it also has a different qualitative significance. The knowledge gained as a result of investigations in Japan is compared with that of conditions in the north-eastern Appalachians, where the climate is very similar to that of Japan in region 3. Here, too, periglacial forms appear regularly within the upper woods. As a preliminary hypothesis it is assumed that within the perenially humid, temperate and subtropical climate zones one may generally differentiate between the following regions (fig. 3): 1. Mountain ranges with a difference of less than 15°C between the average temperature of the warmest and cold est months (temperature amplitude) and a lower boundary of the periglacial stage above the timber-line. 2. Mountain ranges with a temperature amplitude between15° and 22 °C and a lower boundary of the periglacial stage at the altitude of the timber-line. 3. Mountain ranges with a temperature amplitude above 22°C and a lower boundary of the periglacial stage below the timber-line, i.e. with periglacial forms appearing regu larly within the upper woods. So far mountain ranges of region 3 have been studied the least.